The prevalence of comorbidities among adult people diagnosed with HIV infection in a tertiary care hospital in western Saudi Arabia. Issue 11 (November 2020) - Farahat, Fayssal M.; Alghamdi, Yousef S.; Farahat, Amr F.; Alqurashi, Anhar A.; Alburayk, Abdullah K.; Alabbasi, Abdullah A.; Alsaedi, Asim A.; Alshamrani, Majid M.
Abstract: Background: The life expectancy of people living with HIV is markedly increasing with the introduction of effective antiretroviral medications. However, these patients face an increased risk of developing multi-morbidities-especially with advanced age. This study was conducted to assess the prevalence of and risk factors associated with the occurrence of chronic comorbidities among patients diagnosed with HIV infection. Methods: A retrospective chart review was conducted on the medical records of patients with HIV diagnoses from 2000 to 2018. Data were collected on age, sex, date of diagnosis, associated co-morbidities, antiretroviral medications (ART) and status at time of data collection (alive or deceased). Only adult patients 18 years or above were studied. Results: A total of 130 confirmed HIV cases were included. Patient ages ranged from 23 to 86 years old (mean ± SD 50.1 ± 12.6). Almost half of the patients (48.5%) had at least one associated comorbidity. The most common chronic comorbidity was diabetes mellitus (15.4%), followed by dyslipidemia (10.8%), hypertension (10.8%) and lymphoma (10.0%). Comorbidity proportions increased with advanced patient age ( p = 0.047). Three or more comorbidities were reported in 40.7% of patients aged 60 years old or above. Using logistic regression analysis, only patients aged 50 years old or above were more likely to have at least one comorbidity (OR = 7.59, 95%CI = 2.25, 25.61). Conclusions: The burden of chronic comorbidities among people diagnosed with HIV is high, especially among older age individuals, with an increasing number of comorbidities per patient. Proper counseling for HIV patients is highly recommended-not only for prevention of other infectious diseases (e.g., vaccination) but also for lifestyle modification and self-management for those with chronic conditions.